"Plate-like" subsidence of the East Pacific Rise-South Pacific superswell system - Hillier, J; Watts, A (2004)
In previous studies the removal of small-scale features such as seamounts and oceanic islands from bathymetry has revealed a large and unusually shallow region in the South Pacific Ocean, which, at 3000 km wide and up to 1 km high, has been dubbed a "superswell". These studies use statistical techniques based on finding the modal depth of the bathymetry. Such an analysis, however, does not completely isolate these features, or their associated oceanic plateaus and localized hot spot swells, from the ridge-generated regional bathymetry upon which they are superimposed. Accordingly, a technique is required that passes beneath topographic constructs rather than through them, as is the tendency of the mean, median, or mode. We have developed an algorithm, MiMIC, that reproducibly removes all these features and reveals the large-scale bathymetric trends in a manner based upon and consistent with manual interpretation. Application of the algorithm to bathymetry data in the southwest Pacific shows that the depth anomaly with respect to a cooling plate model changes steadily from being too deep at the East Pacific Rise (EPR) crest to being too shallow at the superswell. The largest shallow anomaly of 712 ± 66 m occurs at 98 Ma, not 1300 m at 65 Ma, as has been previously suggested. Most significantly, the superswell appears to be part of a large-scale, " plate-like," subsidence that extends to the EPR crest, rather than an isolated shallowing that reverses the subsidence and causes uplift. We interpret the plate-like subsidence as due in part to cooling of the oceanic lithosphere and in part to a lateral temperature gradient in the underlying asthenosphere which is maintained by the flow of relatively hot material from beneath the superswell toward the relative cold material beneath the EPR. The best fit model implies a lateral temperature gradient of 0.014°C km-1 and is in general accord with the available effective elastic thickness, crustal thickness, heat flow, and seismic tomography data. Copyright 2004 by the American Geophysical Union.